Complete genome sequence of the plant-associated Serratia plymuthica strain AS13. Issue 1 (July 2012) - Neupane, Saraswoti; Finlay, Roger; Kyrpides, Nikos; Goodwin, Lynne; Alström, Sadhna; Lucas, Susan; Land, Miriam; Han, James; Lapidus, Alla; Cheng, Jan-Fang; Bruce, David; Pitluck, Sam; et al.
Abstract Serratia plymuthica AS13 is a plant-associated Gammaproteobacteria, isolated from rapeseed roots. It is of special interest because of its ability to inhibit fungal pathogens of rapeseed and to promote plant growth. The complete genome ofS. plymuthica AS13 consists of a 5, 442, 549 bp circular chromosome. The chromosome contains 4, 951 protein-coding genes, 87 tRNA genes and 7 rRNA operons. This genome was sequenced as part of the project entitled "Genomics of four rapeseed plant growth promoting bacteria with antagonistic effect on plant pathogens" within the 2010 DOE-JGI Community Sequencing Program (CSP2010).